Diagnosis of Small Intestinal Disorders in Dogs and Cats - Allenspach, Karin (Vet Clin North Am Small Anim Pract, 2013)
Laboratory tests are an important part of the workup of small intestinal diseases in dogs and cats. Especially in chronic cases, when extragastrointestinal causes need to be ruled out, it is important to adhere to a systematic workup. This article details the newest available data on tests to aid this diagnostic process. Once the diagnosis of a chronic enteropathy is made, there are many laboratory tests that can help in monitoring the disease and providing prognostic information. Several new tests being evaluated for clinical usefulness are discussed.